The potential of neem, Azadirachta indica A. Juss., for controlling postflowering pests of cowpea, Vigna unguiculata Walp. Maruca testulalis, the pod borer - Jackai, L.E.N.; Oyediran, I.O. (Springer, 1991)
Neem oil (NO), and different formulations of neem oil in a solution of Tetrapleura tetraptera as emulsifier, including neem oil emulsifiable concentrate (NOEC), neem oil slurry emulsifiable concentrate (NOSEC) and 5% NOEC obtained from the seeds of the neem plant, were tested for their efficacy in the control of Maruca testulalis Geyer, under laboratory conditions using flowers of Ife Brown, cowpea variety.